2014
DOI: 10.1186/1472-6831-14-50
|View full text |Cite
|
Sign up to set email alerts
|

Agreement between cranial and facial classification through clinical observation and anthropometric measurement among envigado school children

Abstract: BackgroundTo evaluate the agreement between cranial and facial classification obtained by clinical observation and anthropometric measurements among school children from the municipality of Envigado, Colombia.MethodsThis cross-sectional study was carried out among 8-15-year-old children. Initially, an indirect clinical observation was made to determine the skull pattern (dolichocephalic, mesocephalic or brachycephalic), based on visual equivalence of right eurion- left eurion and glabella-opisthocranion anthro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 24 publications
1
8
0
Order By: Relevance
“…26 It was the least common among (4.32%) Thai 24 and Japanese populations as well. 3 A study done among Colombian population found that the mesocephalic was the second common type of head 27 which was comparable to the present study. But a study conducted in Romanian population and reported the dominant cranial type in their study as mesocephalic.…”
Section: Discussionsupporting
confidence: 90%
“…26 It was the least common among (4.32%) Thai 24 and Japanese populations as well. 3 A study done among Colombian population found that the mesocephalic was the second common type of head 27 which was comparable to the present study. But a study conducted in Romanian population and reported the dominant cranial type in their study as mesocephalic.…”
Section: Discussionsupporting
confidence: 90%
“…(20) In Africans, leptoprosopic face was considered to be the commonest type of face. (25) In both Serbian adult male and female population, leptoprosopic face was the commonest type of face (81.7%), and was followed by mesoprosopic face type, hyperleptoprosopic face type. (3) In Iranian males, mesoprosopic phenotype face was in 38.4% of subjects, whereas in females, euryprosopic face was in 51.7% of subjects.…”
Section: Discussionmentioning
confidence: 99%
“…Although indirect methods of anthropometric measurements have been used, the gold standard is still considered to be the direct in-vivo technique, which is conventional and low-cost. This quantitative method allows an accurate measurement of hair-covered areas and lacks the risk of causing distorted views that are occasionally caused by photographic images used in indirect anthropometry [23,33]. Pouya et al compared the direct and indirect anthropometric measurements for the analysis of cephalofacial dimensions and found that the mean cranial length of males was higher than females.…”
Section: Discussionmentioning
confidence: 99%
“…As a negligible difference was found between the two techniques, they suggested using the robust and low-cost direct anthropometric methodology for constructing more extensive normative databases [29]. A complete assessment of the craniofacial region, consisting of the shape and form of cranium and face, can be performed thoroughly by using anthropometrical indices derived from craniofacial measurements [9,33]. In recent anthropometric studies of the face, the results showed that total facial height, upper facial height, and facial width of males were higher than those of females.…”
Section: Discussionmentioning
confidence: 99%